NEGARA DALAM TINJAUAN AL-QUR’AN - Asrori Mukhtarom; Priyo Susilo (Universitas Muhammadiyah Tangerang, 2019)
There are thousands of verses in the Koran, and many verses have been discussing the definition, meaning, purpose, and form of a state. By way this essence, it is clear that the Qur'an also considers the importance of the existence of a state for human being. Furthermore, his fact also states that for people who believe in the Qur‟an must have attention and responsibility for the development of a state. According to the Qur‟an, the term